Magnetic field decay in young radio pulsars - Igoshev, Andrei P.; Popov, Sergei B. (Astronomische Nachrichten, 2021)
The role of magnetic field decay in normal radio pulsars is still debated. In this paper, we present results which demonstrate that an episode of magnetic field decay in hot young neutron stars can explain anomalous values of braking indices recently measured for more than a dozen of sources. It is enough to have few tens of per cent of such hot neutron stars in the total population to explain observables. Relatively rapid decay operates at ages ≲ few ×100 kyrs with a characteristic timescale of a similar value. We speculate that this decay can be related to electron scattering off phonons in neutron star crusts. This type of decay saturates as a neutron star cools down. Later on, a much slower decay due to crustal impurities dominates. Finally, we demonstrate that this result is in agreement with our early studies.